Fair and Inclusive Markets : Why Dynamism Matters. (IMF Working Papers; Working Paper ;, 2021)
We show empirical evidence that there may not be a tradeoff between market income inequality and high sustained growth, which is key for poverty alleviation. We argue that the economies that achieved high sustained growth and low market income inequality are characterized by dynamism-a drive toward sophisticated export industries, innovation, and creative destruction and a high level of competition. What a country produces and how much it competes domestically and internationally are important for achieving fair and inclusive markets. We explore policy options to steer industrial and market structures toward providing growth opportunities for both workers and firms.